2018
DOI: 10.1002/ange.201806565
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Fluorescence of Metabolite Amyloids Allows Label‐Free Monitoring of Their Formation and Dynamics in Live Cells

Abstract: The formation of apoptosis‐inducing amyloidal structures by metabolites has significantly extended the “amyloid hypothesis” to include non‐proteinaceous, single metabolite building blocks. However, detection of metabolite assemblies is restricted compared to their larger protein‐based counterparts owing to the hindrance of external labelling and limited immunohistochemical detection tools. Herein, we present the detection of the formation, dynamics, and cellular distribution of metabolite amyloid‐like structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The self-assembly of phenylalanine in aqueous solution was initiated by cooling a supersaturated solution of phenylalanine (40 mg/ml) at 90 °C to 20 °C, similar to previous work. 10 This leads to the formation of elongated fibrillary aggregates, as shown by bright-field microscopy (Figure 4a). The phenylalanine fibrils exhibited relative high fluorescence emission in the visible spectral range, which is absent in the monomeric state of phenylalanine, and characterized by the wavelength-dependent Stokes shift, i.e.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The self-assembly of phenylalanine in aqueous solution was initiated by cooling a supersaturated solution of phenylalanine (40 mg/ml) at 90 °C to 20 °C, similar to previous work. 10 This leads to the formation of elongated fibrillary aggregates, as shown by bright-field microscopy (Figure 4a). The phenylalanine fibrils exhibited relative high fluorescence emission in the visible spectral range, which is absent in the monomeric state of phenylalanine, and characterized by the wavelength-dependent Stokes shift, i.e.…”
Section: Resultsmentioning
confidence: 93%
“…[7][8][9] It was shown that single amino acids in their aggregated form can also produce a fluorescent signal, which is not evident in the monomeric state. [10][11][12][13] Numerous observations suggest that the optical phenomenon of aggregation induced intrinsic fluorescence is broader than originally speculated, as it also applies to many other metabolites and nucleic acids. [14][15][16][17][18][19] Circumstantial evidence and argumentation suggested that supramolecular packing is important.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, we focus on the fabrication of biological nanomaterials by controlling the self-assembly of a biomolecule through internal biomolecular interactions and external stimulations. The main used/studied biomolecules, including proteins [ 7 , 41 ], peptides [ 42 , 43 ], amphiphiles [ 44 ], DNA [ 45 ], carbohydrates, metabolites [ 46 , 47 , 48 ], lipids, and cholesterol, for the self-assembly of various nanostructures are introduced and discussed in detail. In Section 2 , some recent studies are analyzed and discussed to illustrate the self-assembly mechanisms of various biomolecules, in which the strategies for creating biological nanomaterials via internal interactions are presented.…”
Section: Introductionmentioning
confidence: 99%